Out-of-pocket expenditure in Indonesia’s national health insurance: evidence from household survey in Bandar Lampung City, Indonesia - Akhmad, Atika Dalili; Setyawan, Irfanianta Arif; Dirga (Pharmacy Reports, 2025)
Indonesia’s National Health Insurance (NHI) was established to promote equitable access to healthcare and protect households from financial hardship. However, out-of-pocket (OOP) payments continue to occur, leading in catastrophic health for many families. This study aimed to measure the incidence and identify the determinants of OOP spending among NHI participants in Bandar Lampung. A cross-sectional survey involving 253 NHI members was conducted in 2020 across clinics, public health centers, and pharmacies. Data were analyzed using chi-square and logistic regression. OOP spending was reported by 31.62% of respondents. Bivariate analysis indicated that the type of health facility (p = 0.004) and membership status (p = 0.040) significantly influenced OOP expenditure, while age, gender, education, occupation, income, and treatment class were not significant. Multivariate analysis confirmed that visits to clinics (p = 0.018) and membership in Mandiri or PBI groups (both p = 0.039) were associated with a higher likelihood of OOP payments. Despite essential health services being covered under NHI, OOP expenditure remains a considerable financial burden. These findings highlight the need for stronger policy interventions to improve benefit coverage and ensure equitable financial protection under Indonesia’s NHI system.